Individualism vs. socialism - Newell, S.B. (My University, 1897)
Introduction: The term Socialism has been connected with so many revolutionary schemes that it now commonly has joined with it a very destructive idea. It should not necessarily have any affinity for violence or confiscation but rather the opposite. In this discussion historical assertions will be eliminated and the true principle advanced. Laissez faire embodies the idea of Individualism. Opposed to this is Socialism. The Socialist holds that society is an organic whole, one individual is dependent on another and thus all are connected with each other, the Individualist on the other hand says it is a disconnected and waring body each working individually and for his own good only. Co-operation rules Socialism; competition Individualism. The one says society should work for a common end and try to help all; the other affirms the idea of man versus man or work simply for your own good. Socialism work for public welfare Individualism for private gain. If all persons were equal in power and ability the two principles would lead to the same results. As life becomes more and more complex this problem increases in importance and the weak should be aided by the strong. The strength of the individuals decides the power of the whole body of society. If one is weak the whole of society is injured to that extent.
Citation: Newell, S.B. Individualism vs. socialism. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: Philosophy; Individualism; Socialism; Theses; Manuscripts (documents)